Tasting Difference : Food, Race, and Cultural Encounters in Early Modern Literature - Shahani, Gitanjali (Book collections on Project MUSE., 2020)
"Examines the colonial histories of everyday foods like sugar, spices, and coffee, arguing that that it is in the writing on food and eating that we see among the earliest configurations of racial difference"--